The Lack of Convergence of Latin-America Compared with CESEE : Is Low Investment to Blame? - Bakker, Bas.; Ghazanchyan, Manuk; Ho, Alex.; Nanda, Vibha (Washington, D.C. : International Monetary Fund, 2020)
In the last few decades there has been little convergence of income levels in Latin America with those in the United States, in sharp contrast with both emerging Asia and emerging Europe. This paper argues that lack of convergence was not the result of low investment. Latin America is poorer because of lower human capital levels and lower TFP-not because of a lower capital-output ratio. Cross-country differences of TFP in turn are associated with differences in human capital, governance and business climate indicators. We demonstrate that once levels of human capital and governance are taken into account, there is strong conditional cross-country convergence. Poor countries with high levels of human capital, governance or business climate indicators converge rapidly. Poor countries without those attributes do not. We show that low investment is the result of low TFP and thus GDP growth-not the cause.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet